How to survive a scandal - Merrill, Christine (Society's most scandalous, 2022)
A sexy Regency romp He's walked right into The gossip of the Season! Captain William Grosvenor's body may be recovering from battle, but his survivor's guilt remains. The last thing he should be doing is kissing mysterious maids in carriages. Especially when that "maid" is in fact debutante Lady Annie Fitzroy! Sparring with adventurous Annie is exhilarating, but it's also dangerous. Because the biggest scandal of the Season is about to explodeand Annie is at the heart of it!